Effect of Increased Endometrial Thickness and Implantation Rate by Granulocyte Colony-Stimulating Factor on Unresponsive Thin Endometrium in Fresh In Vitro Fertilization Cycles: A Randomized Clinical Trial - Fatemeh Sarvi; Marjan Arabahmadi; Ashraf Alleyassin; Marzieh Aghahosseini; Marzieh Ghasemi (Obstetrics and Gynecology International)
Background. The correlation between endometrial thickness and receptivity has been mentioned in various studies. This study investigated the effect of granulocyte colony-stimulating factor in treating thin endometrium of infertile women who were chosen for in vitro fertilization in our infertility clinic in 2014 and 2015. Methods. In this randomized clinical trial, 28 women who were chosen for in vitro fertilization and had endometrial thickness of less than 6 mm on the day of human chorionic gonadotropin (hCG) injection were included in the study. They were randomly divided into two groups: investigation and control groups. In investigation group (n=13) one granulocyte colony-stimulating factor vial (300 micrograms in 1 mL) was infused into the uterus within five minutes by embryo transfer catheter. In control group (n=15) 1 mL of saline was injected into the uterus with the same catheter. Results. There were significant differences between the two groups in terms of means of endometrial thickness on oocyte retrieval day (P=0.001), embryo transfer day (P=0.001), hCG injections (P=0.001), and implantation rates (P=0.001). Conclusion. Granulocyte colony-stimulating factor can increase endometrial thickness in women treated with in vitro fertilization. RCT Code is 201406046063N2.